Analisis Pengaruh Investasi, Pertumbuhan Ekonomi, Dan Konsumsi Terhadap Pendapatan Perkapita Di Indonesia - Maharani, Selvia Dewi; Boedirochminarni, Arfida (Program Studi Ekonomi Pembangunan Universitas Muhammadiyah Malang, 2024)
This research aims to determine the influence of investment, economic growth, and consumption on per capita income in Indonesia from 1990-2022. The research method used is quantitative research using time series data. The data used in this research was obtained from the World Bank. The variables used in the analysis are investment, economic growth, and consumption. The software used to carry out the study is E-views 12. The research results show that the investment variable has a positive and significant effect on per capita income, and the economic growth variable has a positive and significant impact on per capita income. The consumption variable has a negative and significant effect on per capita income.